Improved rovibrational constant for the v12 band of C2H3D - Lebron, Gissela B. (Animo Repository, 2011)
The Fourier transform infrared absorption spectrum of the ν 12 fundamental band of ethylene-d (C2H3D) was recorded at an unapodized resolution of 0.0063cm −1 in the 1330–1475cm −1 region. Upper state (ν 12 =1) rovibrational constants inclusive of three rotational, five quartic, and four sextic centrifugal distortion constants were improved by assigning and fitting 1444 infrared transitions using Watson’s A-reduced Hamiltonian in the I r representation. The present analysis yielded more higher-order upper state constants than previously reported. The rms deviation of the fit is 0.00055cm −1 . Improved ground state rovibrational constants were also determined from the combined fit of 2026 ground state combination differences (GSCD) from the assigned infrared transitions of the ν 12 , ν 3 and ν 6 bands and 21 microwave frequencies of C2H3 D. The rms deviation of the GSCD fit is 0.00047cm −1 . The A-type ν 12 band is centered at 1400.76262±0.00004cm −1 . Local frequency perturbations were not detected in the analysis. The calculated inertial defect Δ 12 is 0.20809±0.00003μÅ 2 .